Female athlete triad epidemiology among adult athletes: A systematic review - Almousa, S.; van Loon, A. B. (Science & Sports, 2024)
Introduction Sports participation has been shown to have many benefits. However, along with the many benefits of sporting activity, it seems that female athletes may experience symptoms related to a condition called the female athlete triad. The purpose of this review is to evaluate the studies that determined the prevalence of the Female Athlete Triad conditions (low Energy Availability (EA), Disordered Eating (DE), Menstrual Disorders (MD), and low Bone Mineral Density (BMD)) in female adult athletes.